Case study: the introduction of a new bean variety in La merced - Ashby, Jacqueline A.; Herpen, D. van (International Center for Tropical Agriculture, 1991)
An exercise aiming at attitudinal sensitization using gender as variable is given. Such exercise consists of the reading of two texts on the introduction of a new bean var. in La Merced, Colombia, and then answering several questions. (CIAT)